Lideranças distribuídas em uma escola do Programa Ensino Integral do Estado de São Paulo - Rodrigues, Esleide de Cassia (2024)
The theme of this dissertation refers to distributed leaderships in a school of the Sao Paulo State Integral Teaching Program, understanding them as a collective phenomenon, in which responsibilities and influences are shared by several school agents. The research on which it is based has been developed within the scope of a larger investigation, conducted by several members of the Study Group on School Organization: Democracy, Human Rights and Administrators Training, denominated Improvement of school climate and development of democratic school leadership in four schools in the Sao Paulo State Integral Teaching Program. Thus, the problem investigated unfolds into two questions: how are the leaderships distributed across the administration team, teachers, staff, students and families? And, how can such leaderships contribute to participative and democratic school administration? The working hypothesis was that the program would enable the distribution of leaderships among its different segments, through the implementation of its guidelines in schools and the expansion of administration teams. The objective was to identify the leaderships distributed in that school, to try to understand their characteristics and their possible contributions to participative and democratic school administration. To this end, a qualitative, descriptive and exploratory methodological path was delimited for the collection of empirical data, through observations and semi-structured interviews, which enabled the collection of data that are analyzed in light of the theoretical framework adopted. It was possible to conclude that the distributed leaderships in that school were characterized as emerging due to activities prescribed by the Program, such as class leadership, tutoring, youth protagonism, pedagogy of presence, in addition to regular school boards, such as the school council and the student union. With regard to the school’s professionals, the extended administration team, prescribed by the Program, composed of principal, vice principal, area and general coordinators, already characterizes, in itself, a certain distribution of leadership that ended up spreading as well among teachers, due to their exclusive full-time dedication to the school, which provided times and spaces that favored the appropriation and construction of leadership practices in relation to students, their peers and the administration team itself. Also noteworthy was the assumption of leadership roles by staff and parents. Regarding the characterization of these leaderships, we may understand them as predominantly participative and democratic, due to evidence that they shared educational objectives and decision-making through egalitarian dialogue in which all voices were equally valued. Also, it stood out that, in the context of the school studied, distributed leadership emerged from both bottom-up interactions – within the different school segments, and top-down, due to the organizational prescriptions of the Program. However, even when distributed by delegation, it was observed that the leaderships acted in the sense of valuing the participation of all school agents, which strengthened leadership practices by the entire school community towards the participation growth among all school agents.